Canonical and Non-Canonical Functions of the Autophagy Machinery in MHC Restricted Antigen Presentation - Münz, Christian (Frontiers in Immunology, 2022)
Macroautophagy delivers cytoplasmic constituents for lysosomal degradation. Since major histocompatibility complex (MHC) class II molecules sample peptides after lysosomal degradation for presentation to CD4+ T cells, it was originally described that these peptides can also originate from macroautophagy substrates. In recent years it has become clear that in addition to this canonical function of the macroautophagy machinery during MHC class II restricted antigen presentation at least parts of this machinery are also used to regulate phagocytosis of antigens, degradation of MHC class I molecules, and unconventional secretion of antigens in extracellular vesicles, including virus particles. This review discusses how both canonical and non-canonical functions of the macroautophagy machinery influence antigen presentation on MHC class I and II molecules to CD8+ and CD4+ T cells. A better understanding of the molecular mechanisms by which the macroautophagy machinery is distributed between its canonical and non-canonical functions should allow targeting of antigens to these different pathways to influence MHC restricted presentation during vaccination against infectious diseases and tumors.